2005
DOI: 10.1143/jjap.44.3364
|View full text |Cite
|
Sign up to set email alerts
|

Design of Slider and Suspension for 4×1 Probe Array Type Near-Field Scanning Optical Microscope

Abstract: Many information storage devices have been introduced and developed in recent years. The trend for these devices is toward high capacity, compact size, low power consumption, reliability, and removability for data interchange with other devices. In addressing these trends, the near-field scanning microscope (NSOM) technique is in the spotlight as the next generation device. In order for a near-field device to be successfully implemented in a system, a slider and suspension must be introduced as actuating mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Many research groups have reported various types of recording methods based on scanning tunneling microscopy (STM) [4,5], atomic force microscopy (AFM) [6][7][8][9][10], and scanning near-field optical microscopy (SNOM) [11,12], etc. Moreover, in order to increase the data transfer rate, parallel data processing using a probe array, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have reported various types of recording methods based on scanning tunneling microscopy (STM) [4,5], atomic force microscopy (AFM) [6][7][8][9][10], and scanning near-field optical microscopy (SNOM) [11,12], etc. Moreover, in order to increase the data transfer rate, parallel data processing using a probe array, i.e.…”
Section: Introductionmentioning
confidence: 99%